Preliminary genome-wide association study for skin traits in an Angora x creole backcross population - Cano Pereira, Ema Margarita; Debenedetti, Sebastián; Giovannini, Nicolas; Taddeo, Héctor Raúl; Poli, Mario Andres (Masey University (Nueva Zelanda), 2022)
Angora goat produce mainly mohair fiber but the Creole goats have a double hair coat: cashmere, fine and short seasonal down coat and coarser and longer guard hair. Both, mohair and cashmere fiber are determined by two types of skin hair follicle, primary and secondary and several phenotypes can be drawn from them like S/P ratio. The aim of this study was to identify polymorphisms associated with skin traits in a backcross Angora x Creole goats (n=477) using a SNP-based GWAS analysis. Significant regions on CHIR 1, 2, 6, and X exhibit a maximum signal for seven SNP markers with a p-value from 8.16E-06 to 1.26E-04. These results indicate that may be several genes that could be involved in skin traits close to the most significant SNP markers in this backross Angora x Creole population.